Simulasi Sensor Radiasi Matahari dengan Algoritma ANFIS menggunakan MATLAB - Muhammad, Umar (Politeknik Bosowa, 2024)
Solar energy has become one of the renewable energy sources that can be converted into electrical energy. Solar cells are used to convert solar energy into electrical energy. Solar radiation is an important factor to consider in the use of solar cells or solar power generation systems. Therefore, it is necessary to develop a solar radiation measurement device. This research is a simulation of a solar cell as a solar radiation sensor using the ANFIS algorithm to calculate the solar radiation value based on the voltage and current from the solar cell. The simulation, conducted using Matlab with solar cell features, a 12-ohm resistor, ANFIS features, and a Fuzzy block, showed good results with an error rate of 0.038 percent. Future research development will involve testing on actual solar cell devices